The role of ethnicity in the upper airway in a Belgian paediatric population with obstructive sleep apnoea. Issue 4 (5th October 2017) - Slaats, Monique; Vos, Wim; Van Holsbeke, Cedric; De Backer, Jan; Loterman, Dieter; De Backer, Wilfried; Boudewyns, An; Verhulst, Stijn
Obstructive sleep apnoea (OSA) occurs in up to 4% of children in the general population [1]. The pathophysiology is likely to be multifactorial because of the high incidence of residual OSA after adenotonsillectomy. There are several risk factors such as obesity, a family history of OSA, male sex, sickle-cell disease, cerebral palsy, and other conditions that may lead to narrowing of the upper airway (UA), such as Down syndrome [2]. Numerous studies of different samples have shown an association between craniofacial skeletal morphology and UA dimension in patients with OSA compared to patients without OSA [3, 4]. A growing body of literature around the world also reports substantial ethnic disparities in the prevalence, degree and treatment of OSA [5–13]. Several US studies concluded that African American (AA) children were associated with more severe OSA in children [5–12]. Buxbaum et al . [11] investigated the difference in OSA severity between Caucasians and AA families (children and adults, n=1915), and showed that there is an underlying genetic basis for OSA in AA children (independent of the contribution of body mass index (BMI)). Stepanski et al . [12] investigated sleep and respiratory parameters in 198 children with and without sleep-disordered breathing (SBD). They reported that AA children with SBD had more severe oxygen desaturation with obstructive events and increased risk of cardiovascular consequences compared to Caucasian children. Marcus et al . [7] concluded that AA children are more likely to have residual disease after surgery than Caucasian children. Tamanyan et al . [13] determined whether demographic or clinical factors predict OSA severity in 301 Australian children. They concluded that non-Caucasian children were more likely to be diagnosed with moderate-to-severe OSA than Caucasian children. Furthermore, there are no studies that compared Asian with Caucasian children with OSA. Upper airway volume between the uvula and epiglottis is smaller in African compared to European children with OSA http://ow.ly/AgoR30evNCu